Pengaruh Partisipasi Anggaran, Informasi Asimetris Dan Budget Emphasis Terhadap Slack Anggaran - Elsa Meirina; Afdaluddin Afdaluddin (JURNAL PUNDI, 2018)
Budget slack is a behavior of individuals and organizations in preparing budgets even more so if the budget is used as a basis for performance measurement. The occurrence of a budget slack, namely budgetary slack will make the performance look better in the eyes of superiors if they can achieve the budget goals. Budgetary slacks are often used to overcome uncertainties predicting the future and the allocation of resources will be carried out based on the projected budget costs, so that slack makes flexible. Budgetary participation, asymmetric information, and budget emphasis are factors that influence the occurrence of budget slack. The study was conducted at the Badan Perencanaan dan Pembangunan Daerah (BAPPEDA) of West Sumatra with a total of 50 respondents consisting of heads of departments, heads of fields, sub-sections, and other employees related to the budget. Data sources in this study are questionnaires that use multiple regression analysis. The results of the research that have been conducted show that asymmetric information affects the occurrence of budget slack. Information owned by subordinates or superiors is the basis for setting the markup level on the budget.